DNA import competence and mitochondrial genetics - Weber-Lotfi, F.; Mileshina, D.V.; Ibrahim, N.; Koulintchenko, M.V.; D'Souza, G.; Saxena, V.; Konstantinov, Yu.M.; Lightowlers, R.N.; Dietrich, A. (Вiopolymers and Cell, 2014)
Aim. To understand the mechanism(s) underlying mitochondrial competence for DNA uptake and to exploit these pathways for the development of in vivo models of gene therapy. Methods. DNA uptake into isolated mitochondria from plant or from mutant Saccharomyces cerevisiae defective for mitochondrial proteins and carriers, biochemical approaches and transfection of mammalian cells with DNA bound to mitochondriotropic liposomes. Results. Special focus on the inner membrane showed the involvement of isoforms of the adenine nucleotide translocator and the contribution of proteins controlling mitochondrial morphology in DNA uptake into yeast organelles. Transfection assays led to significant incorporation of a mitochondrial construct into mammalian cells and expression of a marker gene. Conclusions. The data imply that there are multiple mitochondrial DNA import pathways. On the other hand, preliminary results suggest that mitochondriotropic liposomes can deliver DNA to mitochondria in live mammalian cells.